Hydrophobic Optimization of Functional Poly(TPAE-co-suberoyl chloride) for Extrahepatic mRNA Delivery following Intravenous Administration - Xueliang Yu; Shuai Liu; Qiang Cheng; Sang M. Lee; Tuo Wei; Di Zhang; Lukas Farbiak; Lindsay T. Johnson; Xu Wang; Daniel John Siegwart (MDPI AG, 2021)
Messenger RNA (mRNA) has generated great attention due to its broad potential therapeutic applications, including vaccines, protein replacement therapy, and immunotherapy. Compared to other nucleic acids (e.g., siRNA and pDNA), there are more opportunities to improve the delivery efficacy of mRNA through systematic optimization. In this report, we studied a high-throughput library of 1200 functional polyesters for systemic mRNA delivery. We focused on the chemical investigation of hydrophobic optimization as a method to adjust mRNA polyplex stability, diameter, pKa, and efficacy. Focusing on a region of the library heatmap (PE4K-A17), we further explored the delivery of luciferase mRNA to IGROV1 ovarian cancer cells in vitro and to C57BL/6 mice in vivo following intravenous administration. PE4K-A17-0.2C8 was identified as an efficacious carrier for delivering mRNA to mouse lungs. The delivery selectivity between organs (lungs versus spleen) was found to be tunable through chemical modification of polyesters (both alkyl chain length and molar ratio in the formulation). Cre recombinase mRNA was delivered to the Lox-stop-lox tdTomato mouse model to study potential application in gene editing. Overall, we identified a series of polymer-mRNA polyplexes stabilized with Pluronic F-127 for safe and effective delivery to mouse lungs and spleens. Structure-activity relationships between alkyl side chains and in vivo delivery were elucidated, which may be informative for the continued development of polymer-based mRNA delivery.